Optimizing decision making in the apparel supply chain using artificial intelligence (AI) / Calvin Wong, Z. X. Guo, S Y S Leung - Wong, Calvin
Understanding key decision points in the apparel supply chain -- Fundamentals of artificial intelligence techniques for apparel management applications -- Selecting the location of apparel manufacturing plants using neural networks -- Optimizing apparel production order planning scheduling using genetic algorithms -- Optimizing cut order planning in apparel production using evolutionary strategies -- Optimizing marker planning in apparel production using evolutionary strategies and neural networks -- Optimizing fabric spreading and cutting schedules in apparel production using genetic algorithms and fuzzy set theory -- Optimizing apparel production systems using genetic algorithms -- Intelligent sales forecasting for fashion retailing using harmony search algorithms and extreme learning machines -- Intelligent product cross-selling system in fashion retailing using radio frequency identification (RFID) technology, fuzzy logic and rule-based expert system.